Parental Disability and Teenagers' Time Allocation - Charlene M. Kalenkoski; Sabrina Wulff Pabilonia (Institute of Labor Economics (IZA), 2021)
Using the 2003–2019 American Time Use Survey, we examine how living with a parent who has a work-limiting disability is related to teenagers' time allocation. For girls, we find that living with a disabled parent is associated with less time spent on educational activities, including both class time and homework, less time spent on shopping, and more time spent on market work, pet care, and leisure. For boys, living with a disabled parent is associated with less time spent sleeping. In addition, when examining the time spent by girls and boys in two-parent households, we find that the gender of the disabled parent matters. Girls living with a disabled mother in a two-parent household spend less time on educational activities and more time on market work and pet care, suggesting that girls may take on some of a disabled mother's activities. Boys living with a disabled mother in a two-parent household spend more time on homework and less time on housework and caring for household children. However, if their father is disabled, boys spend more time on food preparation and cleanup. Boys living with a disabled father also spend less time with their mother. Thus, there are differences in teens' time use that depend on both the gender of the teen and of the disabled parent, with teen girls likely being worse off than teen boys. Our results suggest that differences in teenagers' time investments are a plausible mechanism for gender differences in intergenerational economic mobility by parental-disability status.
Keywords: I14; I24; J13; J14; J22; 330; disability; gender; time use; teenagers; schooling; homework